Respuesta :
For this case we must find the inverse of the following function:
[tex]g (x) = 2x + 4[/tex]
Replace g(x) with y:
[tex]y = 2x + 4[/tex]
We exchange the variables:
[tex]x = 2y + 4[/tex]
We solve for "y":
We subtract 4 on both sides of the equation:
[tex]x-4 = 2y[/tex]
We divide between 2 on both sides of the equation:
[tex]y = \frac {x} {2} -2[/tex]
We change y by [tex]g ^ {-1} (x)[/tex]:
[tex]g ^ {- 1} (x) = \frac {x} {2} -2[/tex]
Answer:
[tex]g ^ {- 1} (x) = \frac {x} {2} -2[/tex]
Answer:
[tex]f^{-1}=\frac{x}{2} -2[/tex]
Step-by-step explanation:
the inverse function of g(x) = 2x + 4
To find the inverse of a function we replace g(x) with y
[tex]y=2x+4[/tex]
Replace x with y and y with x
[tex]x=2y+4[/tex]
Solve the equation for y
Subtract 4 from both sides
[tex]x-4= 2y[/tex]
Divide both sides by 2
[tex]\frac{x}{2} -2=y[/tex]
[tex]y=\frac{x}{2} -2[/tex]
Replace y with f inverse
[tex]f^{-1}=\frac{x}{2} -2[/tex]